Orthodontic Treatment Needs in Adolescents Aged 13-15 Years Using Orthodontic Treatment Needs Indicators - Tita Ratya Utari; Median Kurnia Putri (Indonesian Dental Association, 2019)
Introduction: The prevalence of malocclusion in Indonesia is still very high, which is about 80% of the population and is one of the major dental and oral health problems. Based on the research result by the Health Research and Development Department, Ministry of Health Republic Indonesia, the highest malocclusion prevalence in children aged 12-15 years is 15.6%. Problems in adolescents aged 13-15 oral cavity, such as disruption of tooth eruption, can cause malocclusion, related function, aesthetics, and quality of life. Objective: To assess orthodontic treatment need in adolescents aged 13-15 years in Muhammadiyah 3 Junior High School of Yogyakarta using Orthodontic Treatment Needs Indicators, the description of malocclusion classification and their correlation. Method: This research is an analytical observational study with cross-sectional design. Samples are 100 students aged 13-15 years in Muhammadiyah 3 Junior High School of Yogyakarta. Each sample fills out an IKPO questionnaire to assess the need for orthodontic treatment needs, examination, and intraoral photographs were taken to determine the malocclusion classification. Results: The results showed 61% of subjects required orthodontic treatment, and 63% had Class I malocclusion, 28% had Class II malocclusion, and 9% had Class III malocclusions. There was a correlation between the questionnaire of orthodontic treatment needs on age with a significant value, 0.037 (p<0.05). Conclusion: More than 50% of adolescents aged 13-15 years at Muhammadiyah 3 Junior High School of Yogyakarta need orthodontic treatment with the highest malocclusions is Class I Angle malocclusion, and there is a correlation between age and orthodontic treatment needs.